2022
DOI: 10.1101/2022.01.27.477975
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comprehensive evaluation of generalizability of deep-learning based Hi-C resolution improvement methods

Abstract: HiC is a widely used technique to study the 3D organization of the genome. Due to its high sequencing cost, most of the generated datasets are of coarse quality, consequently limiting the quality of the downstream analyses. Recently, multiple deep learning-based methods have been proposed to improve the quality of these data sets by increasing their resolution through upscaling. However, the existing works do not thoroughly evaluate these methods using HiC reproducibility metrics across different HiC experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…We compare the performance of GrapHiC against two relevant state-of-the-art methods. First, we compare our performance with HiCNN [8] because a recent evaluation [14] showed that HiCNN provides the best imputation generalizability across a broad range of sparse real-world Hi-C datasets. Second, we compare our performance with HiCReg [30], a method that utilizes the same 1D genomic signals without a sparse Hi-C contact map to impute Hi-C reads.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We compare the performance of GrapHiC against two relevant state-of-the-art methods. First, we compare our performance with HiCNN [8] because a recent evaluation [14] showed that HiCNN provides the best imputation generalizability across a broad range of sparse real-world Hi-C datasets. Second, we compare our performance with HiCReg [30], a method that utilizes the same 1D genomic signals without a sparse Hi-C contact map to impute Hi-C reads.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our Hi-C data, we binned all the data in 10kbp resolution, normalized them in the 0 to 99.75th percentile range, and cropped them into sub-ranges of size 200 that aligned with Hi-C submatrices. We divided chromosome [1][2][3][4][5][6][7][8][12][13][14][15][16][17][18] as training, [8,10,19,22] as validation and [9,11,20,21] as testing chromosome sets. We have summarized our inputs' pre-processing workflow in the Figure 1 A and their statistics in the Supplementary Tables S1, S2, and S3.…”
Section: Datasets and Preprocessingmentioning
confidence: 99%
See 3 more Smart Citations